Future research in humanitarian operations: A behavioral operations perspective (2017)
Behavioral operations have established itself as a mature field of research in operations and supply chain management. Since almost all operational contexts contain people (e.g., managers, employees and customers) who are prone to decision-making errors that can negatively impact performance, behavioral operations can inform models and frameworks in operations management to account for such shortcomings. In this chapter, we explore the application of different methodological tools used in behavioral operations to study behavior in humanitarian logistics and supply chain management (HLSCM). Specifically, the chapter will explore the use of behavioral experiments, system dynamics and agent-based modeling as methodologies to understand decision making in humanitarian operations.